PENGEMBANGAN LKPD BERBASIS ANDROID UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS TRANSAKSIONAL BAHASA JEPANG KELAS X SMK TIGAMA PEKANBARU - Della Febrianita; Mangatur Sinaga; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This is a research on developing Android-based Student Worksheets (LKPD) on watashi no kazoku material. The purpose of this study was to determine the procedure for developing Android-based worksheets on watashi no kazoku material and its level of validation in improving the ability to write Japanese transactional texts for class X according to the assessment of material experts and media experts. The development model used in this research is the ADDIE development model by Dick and Carry. Data obtained from the validation sheet of material experts and media experts. The results of this study indicate that based on the assessment of the two validators, Android-based worksheets to improve the ability to write Japanese transactional texts for Class X are in the valid category. Thus, android-based worksheets on watashi no kazoku material are suitable for use in Japanese class X learning.Key words: Student Worksheets, Writing skills, Japanese Transactional Texts